(untitled) (The Pakistan Development Review, 2001)
Human resource development has assumed primary importance in the development process since the Industrial Revolution. Historical experience indicates that a major share of the wealth of nations is explained by investment in human capital [UNDP, Human Development Report (1996)]. Major developed countries invest billions of dollars in the development of human resources to raise their economic growth rates. The development of Japan is attributed entirely to the development of its human resources. Other Asian countries such as Singapore, Korea, Hong Kong, and Taiwan are also following in the footsteps of Japan in their pursuit of development.